What are the factors behind pay settlements? Evidence from Spanish and British data - Alberto Bayo-Moriones; José Enrique Galdon-Sanchez; Sara Martinez-de-Moretin (Institute for the Study of Labor (IZA), 2008)
This article presents a study of the determinants of pay settlements in a sample of Spanish and British establishments. We find that variables such as establishment size and age, foreign ownership, labour costs, the existence of internal labour markets, a strategic approach to human resource management and pay setting institutions are related to the factors that shape pay adjustments. Moreover, our findings show that there are significant differences in the determinants of pay settlements between Spain and Great Britain. We suggest that the labour market institutions developed in each country influence pay setting decisions.
urn:nbn:de:101:1-2008032034
Keywords: J30; 330; Compensation systems; labor market institutions; wage settlements; establishment level data; Vergütungssystem; Lohnpolitik; Unternehmen; Panel; Arbeitsmarktflexibilisierung; Vergleich; Großbritannien; Spanien